Proyecto de factibilidad para la implementación de una empresa de servicio de lavado en seco en el cantón Lago Agrio, para el año 2015 - Castillo Manchay, Yessenia Amparo (2016)
This project feasibility for the implementation of a service company drycleaning in the canton Lago Agrio, 2015 born as a solution to the problems posed for families and people washing their clothing, as It mentioned the following lack of time, difficulty moving, saving, and service alternatives that are more suitable for treating the clothes, especially when are sensitive materials that can not be wet. Given this need of the inhabitants of Lago Agrio Canton and taking into account that service companies in Ecuador; Latin America and the world are very important as they are dedicated to providing focused on service quality services, has been considered that the implementation of a company drycleaning focused on satisfying these needs, have very good market acceptance and potential customers who are looking for this type of service, satisfying their needs with regard to washing. It should be noted that at present people are raising awareness and seek the replacement of these resources by more efficient through technology, which is why they have created biodegradable substances, processes which allow clean clothes without mistreat them without of water. The thesis takes this concern of people and of these technologies to search for a business opportunity that can be exploited in a dry cleaning company. The completion of this work required the use of investigative techniques, knowledge of market research, marketing, project development among others, with all this we proceed to structure research, focusing on the needs that are to solve and resolve, with the resources available to later start fieldwork as is the development, design and implementation of surveys of the target population, using this information we proceed to tabulate and analyze, with the development of statistical tables and charts that make more understandable the results obtained. Subsequently it investigated everything that involves creating a company drycleaning, determining equipment, machinery, chemicals, personnel, infrastructure, washing processes, types of labels, ie the technical study needed to be feasible implementation and up company. Finally and any information gathered in this study process document supporting the project feasibility in creating the company, taking into account all the requirements for it was developed. Research and development of the document was conducted from March to October 2015, for which he had the work of the author who synthesized, I analyze, I surveyed, Tabulo entire study to finally develop, to serve as bibliographic material for both teachers , students and researchers who perform similar work market research and feasibility studies and need current data from the Lago Agrio canton. From everything done in this thesis is determined that a detailed analysis of the potential that the project feasibility dry cleaning company Clean Yessenia for the canton of Lago Agrio can generate study. The same satisfying partners and investors. Obtained as a result: a feasibility project for the implementation of service dry cleaning in the canton Lago Agrio, where it was determined that potential customers who use or wish to use this service market, the supply of that service is poor there, is a project of feasible investment to make and with a high potential for success in the local market in the future, with low environmental impact, friendly to the environment, and a social impact that contributes to the creation of jobs, improvement of the sector where it was installed, reducing insecurity among other qualities. In addition to that the most appropriate corporate structure for the existing market niche is the Limited Company.